2006
DOI: 10.1186/1476-4598-5-28
|View full text |Cite
|
Sign up to set email alerts
|

Methylation mediated silencing of TMS1/ASC gene in prostate cancer

Abstract: BackgroundTranscriptional silencing associated with aberrant promoter methylation has been established as an alternate pathway for the development of cancer by inactivating tumor suppressor genes. TMS1 (Target of Methylation induced Silencing), also known as ASC (Apoptosis Speck like protein containing a CARD) is a tumor suppressor gene which encodes for a CARD (caspase recruitment domain) containing regulatory protein and has been shown to promote apoptosis directly and by activation of downstream caspases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…1A). No sumoylation sequence is found in the HYAL-1 protein (33). Consistent with this observation, HYAL-1 immunoprecipitation, followed by anti-sumo1 or anti-sumo2/3 immunoblotting, showed that HYAL-1 protein is not sumoylated (data not shown).…”
Section: Transcriptional Regulation Of Hyal-1supporting
confidence: 73%
“…1A). No sumoylation sequence is found in the HYAL-1 protein (33). Consistent with this observation, HYAL-1 immunoprecipitation, followed by anti-sumo1 or anti-sumo2/3 immunoblotting, showed that HYAL-1 protein is not sumoylated (data not shown).…”
Section: Transcriptional Regulation Of Hyal-1supporting
confidence: 73%
“…observed that the CD44 and GSTP1 were not significantly different in terms of their methylation status between populations. However, significantly enhanced methylation of PYCARD (TMS1/ASC) in benign prostatic hyperplasia (BPH) was reported in AA cases (33). Despite these contradictory findings, the importance of epigenetic modifications cannot be undermined.…”
Section: Molecular Bases Of Prostate Cancer Racial Disparitiesmentioning
confidence: 99%
“…Indeed, accumulating information suggests that ASC may play multiple roles in cancer. For example: it can function as a tumor suppressor; its expression is decreased by promote methylation in cancers such as melanoma [23], breast cancer [24], ovarian cancer [25], prostate cancer [26], colorectal cancer [27] and hepatocellular carcinoma [28]; it is reportedly involved in the progression of melanoma [29]; and our group showed that it is highly elevated in NPC tumor cells, where its expression correlates with local recurrence and the survival of patients [22]. These findings prompted us to explore the potential role of inflammasome proteins in OSCC, which is believed to be associated with local inflammation.…”
Section: Introductionmentioning
confidence: 99%